(untitled) (Revista Venezolana de Salud Pública, 2018)
Because the contaminated food borne diseases pose a serious public health problem, the detection of intestinal parasites using appropriate diagnostic techniques is of paramount importance. The objective of this study was to compare the sensitivity of two technique used for detecting intestinal parasites in lettuce distributed in Carabobo state, Venezuela, during the period 2009-2010. Were collected of way non-probabilistic accidental 120 samples of lettuce: 60 of the American variety (Lactuca sativa variety capitata or Great Lakes) and 60 of the Romana variety (Lactuca sativa variety longuifolia or White Paris) which were analyzed by the Álvarez technique modified by Traviezo (AMT) and Takayanagui technique modified (TM). We obtained the following results: by the AMT technique, 15.0% of all lettuces tested positive to some type of intestinal parasites, while by the TM technique 21.7% were positive. Depending on the type of lettuce, the American turned out to be more contaminated by the two techniques: 26.7% for AMT technique and 43.3% for TM technique. The Z test for comparison of two proportions, analyzed by chi-square statistic no showed significant difference between them (Z =- 0.71, p = 0.4791) as was concluded that for the analysis of samples enteroparasitarie contamination of lettuce can be used either of the techniques described.